Impedance interactions in bidirectional cascaded converter. Issue 13 (1st October 2016) - Tian, Yanjun; Loh, Poh Chiang; Chen, Zhe; Deng, Fujin; Hu, Yanting
Abstract : A cascaded converter is built by connecting one elementary converter to another. Output impedance of one converter will therefore interact with input impedance of the other converter. This interaction will change when power flow reverses. To compare this difference, an investigation is performed here for showing that forward and reverse interactions are prominently different in terms of dynamics and stability, even though the cascaded converter control remains unchanged. The concluded findings have been verified by simulation and experimental results, from which, important guidelines have been formulated for the cascaded converter when used in either unidirectional or bidirectional applications.